Factors Affecting Entrepreneurial Intention Of Malaysian University Students - Francis, Chuah; Hiram, Ting; Syed Ridhwan, Alsree; Cheah, Jun-Hwa (2015)
Entrepreneurship development has been designated as a key component in economic transformation and educational programs in Malaysia. The government has introduced various initiatives to cultivate entrepreneurial spirit among younger generations, especially the university students. Despite the magnitude of these efforts, little is known whether university students today are entrepreneurial. Notwithstanding the abundance of literature on entrepreneurship, factors affecting students’ entrepreneurial behaviour and why certain students are more entrepreneurial than others require continual assessment. Hence, the present study is aimed at investigating entrepreneurial intention among university students in Malaysia. Theory of planned behaviour is adopted to specifically look at the effect of behavioural factors on entrepreneurial intention. Moreover, contextual factors are incorporated into the model to articulate the impact of perceived support and barriers towards such intention. Using field data collected from 204 university students in Malaysia, this study examines the impact of behavioural factors as well as the contextual factors on students’ entrepreneurial intention by means of multiple regression using SPSS. The findings show that behavioural factors, namely attitude, subjective norm and perceived behavioural control, have significant effect on entrepreneurial intention. It is also found that perceived positive image about entrepreneurs and perceived difficulty to get financial support have impact on their intention. This confirms the need to inculcate entrepreneurism into university students and highlights the importance of providing them conducive surroundings to allow them to develop as entrepreneurs. It also suggests the misleading mentality among students about entrepreneurship as they might have perceived it to be about doing business with strong reliance on financial resources.